2023
DOI: 10.1590/s1678-9946202365019
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and serological diagnosis of toxoplasmosis: a systematic review and meta-analysis

Abstract: Toxoplasmosis is an infection of vast worldwide distribution whose etiologic agent is Toxoplasma gondii. This disease can cause problems ranging from mild symptoms to serious conditions, such as encephalitis, miscarriage and blindness. Therefore, it is of utmost importance to perform a diagnosis with reproducible techniques in order to obtain a good prognosis. The aim of this review was to analyze the efficiency of toxoplasmosis diagnostic techniques based on sensitivity and specificity results. Five research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…Given that serological tests may result in the overestimation of prevalence via false positive results, a second test should be recommended for further confirmation in epidemiological investigations of toxoplasmosis. Accordingly, a meta-analysis revealed that a combination of tests may improve the sensitivity and provide improved accuracy ( 74 ). Finally, as knowledge of risk factors for toxoplasmosis and toxocariasis may be helpful during early pregnancy ( 44 ), such educational and preventive activities should be taken into consideration as public health policies.…”
Section: Discussionmentioning
confidence: 99%
“…Given that serological tests may result in the overestimation of prevalence via false positive results, a second test should be recommended for further confirmation in epidemiological investigations of toxoplasmosis. Accordingly, a meta-analysis revealed that a combination of tests may improve the sensitivity and provide improved accuracy ( 74 ). Finally, as knowledge of risk factors for toxoplasmosis and toxocariasis may be helpful during early pregnancy ( 44 ), such educational and preventive activities should be taken into consideration as public health policies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the combined use of another serological method (e.g., ELISA) with IFAT could help to better understand the seroconversion dynamics observed herein. According to a meta-analysis, the use of enzyme-linked fluorescent immunoassay, consisting of an immunoenzymatic method with the final fluorescence detection, has provided a 92% sensitivity and 80% specificity for the IgG marker, highly improving the sensitivity accuracy [46].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, It may need to be liquefied, diluted with PCR-quality water, and mixed via a pipette or rotator. (Souza et al 2023).…”
Section: Discussionmentioning
confidence: 99%